Country-Specific Digital Inequalities in Older People’s Online Health Information Seeking in Europe: Impact of Socio-Demographic and Socio-Economic Factors - Aliaksandra Shutsko (Journal of Information Science Theory and Practice, 2022)
Since older people are traditionally considered disadvantaged when it comes to Internet use, it is useful to examine whether older individuals use the Internet for health information seeking (HIS). This study aims to investigate digital inequalities in terms of Internet use by older population for HIS in the European region. As methods, we applied secondary data analysis (of Eurostat data) to investigate the influence of age, educational level, sex, and countries’ wealth. Cluster analysis combined with multidimensional scaling was used to find out those countries exhibiting similarities in older people’s online HIS. The main results are: Older individuals do not equally use the Internet in general and for HIS in particular. Older Internet users with higher level of education and of the female sex are more likely to use the Internet for health information.